2014
DOI: 10.15517/rbt.v53i3-4.14593
|View full text |Cite
|
Sign up to set email alerts
|

Carotenogénesis de cinco cepas del alga <i>Dunaliella</i> sp. (Chlorophyceae) aisladas de lagunas hipersalinas de Venezuela

Abstract: Carotenogenesis of five strains of the algae Dunaliella sp. (Chlorophyceae) isolated from Venezuelan hypersaline lagoons. We evaluated discontinuous cultures (Algal medium at 0.5 mM of NaNO 3 , and 27% NaCl) of five strains of Dunaliella sp. isolated from Venezuelan hypersaline lagoons (Araya, Coche, Peonía, Cumaraguas, and Boca Chica) and one strain from a reference collection (Dunaliella salina, LB1644). Cultures were maintained to 25±1 °C, with constant aeration, photoperiod 12:12, and two light intensities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…Afify et al (2010) found a similar value, 9.2% dw of lipid for the filamentous cyanobacterium Spirulina platensis. There are many reports in the literature of eukaryotic microalgae that responded to nitrogen starvation with expressive increases in lipid production (Lombardi & Wangersky, 1995;Guevara et al, 2005;Chen et al, 2011;Karatay & Dönmez, 2011), contrasting with our study.…”
Section: Gross Chemical Compositioncontrasting
confidence: 99%
“…Afify et al (2010) found a similar value, 9.2% dw of lipid for the filamentous cyanobacterium Spirulina platensis. There are many reports in the literature of eukaryotic microalgae that responded to nitrogen starvation with expressive increases in lipid production (Lombardi & Wangersky, 1995;Guevara et al, 2005;Chen et al, 2011;Karatay & Dönmez, 2011), contrasting with our study.…”
Section: Gross Chemical Compositioncontrasting
confidence: 99%
“…Actually, the increase in lipid content may be species and strain specific (El-Baky et al [ 2004 ]; Pal et al [ 2011 ]; Olofsson et al [ 2014 ]). Dunaliella , Chlorella and Nannochloropsis species are known to respond to nitrogen starvation by increasing lipid production (Lombardi and Wangersky [ 1995 ]; Guevara et al [ 2005 ]; Converti et al [ 2009 ]; Dong et al [ 2013 ]). Also, it is evident that nitrogen is a limiting factor for the growth of many living species (Hansen et al [ 2000 ]; Li et al [ 2010 ]; Park et al [ 2012 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Cifuentes et al [45] and Guevara et al [46] have reported that the environmental conditions may be partly responsible for the development carotenogenesis in a particular strain of Dunaliella spp.…”
Section: Discussionmentioning
confidence: 99%